KEEFEKTIFAN UPAYA MENINGKATKAN MOTORIK KASAR MELALUI SENI TARI JARANAN DI RA AL-HIKMAH KWEDEN - Nisa Nuria; Dema Yulianto; Linda Dwiyanti (Universitas Nusantara PGRI Kediri, 2024)
The purpose of the study was to determine the effectiveness of gross motor skills through Jaranan Dance Art in group B at Ra Al- Hikmah Kweden Kediri Regency. The type of research used is Classroom Action Research (CAR) with the Kemmis & Mc Taggart model. The subjects of this study were 15 group B students at RA Al- Hikmah Kweden, Ngasem District, Kediri Regency. Data collection for case studies is in the form of documents, archival recordings, interviews, observations and physical devices. Activities in this data analysis are by summarizing, selecting key things, focusing on important things to look for themes and patterns (data reduction), then the data is presented in a pattern that is in accordance with the study (data display), and after that a conclusion is drawn that produces a hypothesis and a description or description of an object that was previously dim or dark becomes clear (conclusion drawing) or (verification). The conclusion of the research results obtained from observations and interviews and documentation conducted by researchers, Jaranan Dance activities carried out by group B students at Ra Al-Hikmah Kweden, are very effective in improving gross motor skills of early childhood at RA Al-Hikmah Kweden